Psycho-vegetative and somatic associations in patients with coronary heart disease - T. A. Liman; V. F. Vinogradov; D. V. Alexeev; A. S. Kachalova; R. A. Razygraev (Кардиоваскулярная терапия и профилактика)
This literature review is focused on psycho-emotional status in patients with various clinical forms of coronary heart disease (CHD), as well as the specifics of autonomic regulation and clinical course, including CHD prognosis. The authors describe selected methods for objective dynamic assessment of these characteristics and their interrelations.